2005
DOI: 10.2355/isijinternational.45.1474
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Channeling Factor on Liquid Hold-ups in an Initially Unsoaked Bed

Abstract: One of the important factors for minimum energy consumption and CO 2 emission of a blast furnace (BF) is to elucidate the liquid flow phenomena and liquid hold-ups in the dripping zone of BF. Liquid hold-ups were studied by using a cold model of a fixed bed soaked prior to experiments (hereinafter called initially soaked bed), but the existing correlation equations derived from liquid hold-ups under initially soaked bed do not agree with liquid hold-ups under initially unsoaked bed such as the dripping zone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Even if D p increases up to 40, 50 and 60 mm such as the dripping zone in BF, H S and H t for initially unsoaked bed are estimated at about 90 % of those for initially soaked bed by author's equation. 15) On the other hand, H d in both cases of initially unsoaked (ᮀ) and soaked beds () have almost the same values except for D p ϭ5.4 mm. In the near future, the significant difference in H d for D p ϭ5.4 mm should be investigated.…”
Section: Influence Of Initially Soaked and Unsoaked Bedsmentioning
confidence: 88%
“…Even if D p increases up to 40, 50 and 60 mm such as the dripping zone in BF, H S and H t for initially unsoaked bed are estimated at about 90 % of those for initially soaked bed by author's equation. 15) On the other hand, H d in both cases of initially unsoaked (ᮀ) and soaked beds () have almost the same values except for D p ϭ5.4 mm. In the near future, the significant difference in H d for D p ϭ5.4 mm should be investigated.…”
Section: Influence Of Initially Soaked and Unsoaked Bedsmentioning
confidence: 88%
“…Dynamic holdup is the volume fraction of the liquid in the bed, which drains out from the bed when Kawabata et al reported that when there is no gas injection from the bottom, the static holdup, which is much larger than the dynamic holdup, is a dominant factor determining the total holdup. 8,9) Moreover, when the static and dynamic holdups are investigated simultaneously, the reliability of the obtained results becomes lower. [14][15][16] Therefore, in this study, only the static holdup is considered.…”
Section: Theorymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Shulman et al 2) suggested that the liquid holdup is composed of static and operating (dynamic) hold-up. Because of the difficulties encountered in high temperature experiments, many cold model studies have been widely carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggests that the liquid flow phenomenon comprises various phenomena, such as branching and coalescence of flow paths, which are collections of droplets, deformation of droplets, and the like. 9,10) Accordingly, when attempting to express the total liquid flow, there are limits to the conventional stochastic approach based on a distribution of spheres. Furthermore, wettability with the coke packed bed, the physical properties of the liquid phase, and other factors have a complex effect on the liquid flow in the bottom of the blast furnace.…”
Section: Introductionmentioning
confidence: 99%